1999
DOI: 10.1093/emboj/18.21.6050
|View full text |Cite
|
Sign up to set email alerts
|

The zinc finger protein NRIF interacts with the neurotrophin receptor p75NTR and participates in programmed cell death

Abstract: contributed equally to this work NRIF (neurotrophin receptor interacting factor) is a ubiquitously expressed zinc finger protein of the Krü ppel family which interacts with the neurotrophin receptor p75 NTR . The interaction was first detected in yeast and then biochemically confirmed using recombinant GST-NRIF fusions and p75 NTR expressed by eukaryotic cells. Transgenic mice carrying a deletion in the exon encoding the p75 NTRbinding domain of NRIF display a phenotype which is strongly dependent upon genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 75 publications
5
134
0
Order By: Relevance
“…3), many of them as a result of yeast two-hybrid screens. P75 interactors involved in transducing cell death include a ubiquitously expressed zinc finger protein designated NRIF (neuro-trophin receptor-interacting factor; Casademunt et al 1999). The retinae of nrif−/− mice show reduced cell death, and this reduction is quantitatively similar to that seen in p75−/− and ngf−/− mice.…”
Section: Signal Transduction Through the Neurotrophin Receptor P75mentioning
confidence: 94%
“…3), many of them as a result of yeast two-hybrid screens. P75 interactors involved in transducing cell death include a ubiquitously expressed zinc finger protein designated NRIF (neuro-trophin receptor-interacting factor; Casademunt et al 1999). The retinae of nrif−/− mice show reduced cell death, and this reduction is quantitatively similar to that seen in p75−/− and ngf−/− mice.…”
Section: Signal Transduction Through the Neurotrophin Receptor P75mentioning
confidence: 94%
“…94 Other potential death-mediating p75 NTR interactors include NRAGE 49 and NRIF. 95 Another proapoptotic transmembrane protein has been identified that has a death domain very similar to that of p75 NTR , and this protein interacts with p75 NTR . 96 The protein, dubbed p75 NTR -like apoptosis-inducing death domain protein (PLAIDD) and also referred to as neurotrophin receptor homologue 2 (NRH2), 97 displays a type II death domain (which is structurally slightly different from the type I death domains displayed by death receptors such as Fas and TNFR I) that is closely related to the type II death domain of p75 NTR , with 42% identity.…”
Section: Patched: Hedging Bets On Neural Tube Developmentmentioning
confidence: 99%
“…The mechanism by which p75 activates JNK is still unknown. Although nine different molecules are known to interact with p75 to date, none of them has been linked to the JNK pathway (Casademunt et al, 1999;Chittka and Chao, 1999;Irie et al, 1999;Khursigara et al, 1999;Yamashita et al, 1999;Ye et al, 1999;Salehi et al, 2000). We therefore sought to find an upstream regulator that may be most proximal to the receptor.…”
Section: Rac1 Is An Upstream Regulator In P75-mediated Jnk Activationmentioning
confidence: 99%